The combustion characteristics of Coal Bio-Oil Slurry / Hazlin Hamdan - Hamdan, Hazlin (2016)
Global concerns on suppression of coal consumption for carbon emissions reduction have led to a wide interest on the implementation of coal-biomass co-combustion. Since a complete replacement of fossil fuel-based power generation technologies are capital intensive and unachievable in a short term period, Coal Bio-oil Slurry (CBS) fuel is being proposed in this research as it has strong potential to overcome the drawbacks of direct use of biomass in co-combustion, as bio-oil has much higher energy density and results in less transportation cost. The aim of this research is to investigate the fuel properties of the CBS to be potentially applied in the vast existing coal-fired power plants. Coal at different ranks were blended with bio-oil into several ratios from 90:10 to 50:50 and tested under inert and air atmosphere separately using thermogravimetric analyzer (TGA). The results revealed that the addition of bio-oil has improved the reactivity of the coal blends that lead to an early decomposition at maximum rate of decomposition under pyrolysis condition and improved the combustibility of the slurry blends under combustion condition. The values of pre-exponential factor, A and activation energy, Eₐ were evidently increased with the increasing of bio-oil ratios in the coal blends. Under pyrolysis condition, 90:10 blends appear to be the optimum fuel with highest decomposition rate, while 90:10 blends appear as optimum fuel under the combustion regardless of their high Eₐ value. In overall, Clermont coal has shown greater potential due to its higher heating value and combustibility compared to Adaro coal.